Biodiesel Co-products Modified the Rumen Parameters of Feedlot Lambs but did not Change Methane Production In Vitro* - Romanzini, Eliéder Prates; da Silva Sobrinho, Américo Garcia; Valença, Roberta de Lima; Borghi, Thiago Henrique; Merlim, Fernanda de Almeida; de Andrade, Nomaíaci; Brancacci Lopes Zeola, Nivea Maria; Castagnino, Pablo de Souza; Bernardes, Priscila Arrigucci (Acta Scientiae Veterinariae, 2020)
Background: Intensification of livestock is a strategy that increases productivity, but the diets used to increase animal production efficiency are composed mainly of corn and soybean, thereby increasing competition between animals and humans for the same food crops. This study evaluated nutrient intake, apparent digestibility of dry matter (DM) and nutrients, kinetics of gas production, and concentration of volatile fatty acids on diets with or without inclusion of biodiesel co-products formulated for feedlot lambs. So, the hypothesis is that replace of traditional ingredients by biodiesel co-products changes rumen parameters and methane emissions. Material, Methods & Results: The experiment was developed in São Paulo State University (Unesp), Jaboticabal/SP, Brazil, in Sheep Production Laboratory, which is owned to Animal Science Department. All trials developed in this study used a feedlot system, where animals were kept in individual pen. Forty Ile de France lambs male non-castrated were used in in vivo trial. To obtain rumen fluid, that was used in in vitro trial, four Santa Inês lambs with rumen cannula were used. The treatments evaluated were four diets: Control diet: roughage + concentrate; PM20: roughage + concentrate with peanut meal (PM) at 20% of DM; CG25: roughage + concentrate with crude glycerin (CG) at 25% of DM; and PMCG: roughage + concentrate with PM at 10% of DM and CG at 12.5% of DM. The roughage:concentrate ratio was 40:60 for all these diets. The parameters of the in vitro and in vivo experiments used were completely randomized with four treatments. When significant, the means between treatments were compared using Tukey test (P < 0.05). There was no effect of co-product inclusion on intake, except ether extract and neutral detergent fiber, which were higher for PM20 compared with CG25 diet. Apparent digestibility of dry matter (79.87%) and some nutrients (organic matter, crude protein, and neutral detergent fiber) was higher (P < 0.05) with CG25 diet. In vitro cumulative gas production was greater in CG25 and PMCG compared to the other diets, at early measurement points (2, 4, 6, and 10 h). The concentrations of methane, volatile fatty acids, and acetate:propionate ratio in vitro did not differ (P > 0.05) among diets. Discussion: Probably the high quality of the glycerin used (83.9% glycerol, 12.01% humidity, 3.79% salts, and 0.28% organic matter, no fat, as described by the manufacturer) may explain the low EE concentration observed in the diet using only crude glycerin and the observed lack of DMI effects in all diets. About apparent digestibility, the greater values measured for crude protein can be explained by superior synchronism during fermentation of the proteins and carbohydrates in the diet. The data showed that treatment CG25 obtained higher initial gas production, followed by treatment PMCG which contained 12.5% crude glycerin. Probably these results were caused by the greater apparent digestibility of DM in treatments that included crude glycerin. Our results of volatile fatty acid concentration are different from the decrease in molar proportion of acetic acid and increase of propionic acid described by several authors, with the inclusion of glycerin in the diet. However, the absence of effect by co-product inclusion on the molar proportion of acetic, propionic, and butyric acids measured in this trial reinforce the report from other authors that affirmed the same situation. Hence, the inclusion of PM at 20% of DM and CG at 25% of DM could successfully replace the traditional diets of feedlot lambs such as soybean and corn, respectively, without damages to intake and ruminal parameters in vitro.